The potential of epigallocatechin gallate in the chemoprevention and therapy of hepatocellular carcinoma - Li, Dongming; Cao, Donghui; Cui, Yingnan; Sun, Yuanlin; Jiang, Jing; Cao, Xueyuan (Frontiers in Pharmacology, 2023)
Hepatocellular carcinoma (HCC), one of the most notorious malignancies globally, has a high fatality and poor prognosis. Though remarkable breakthroughs have been made in the therapeutic strategies recently, the overall survival of HCC remains unsatisfactory. Consequently, the therapy of HCC remains a great challenge. Epigallocatechin gallate (EGCG), a natural polyphenol extracted from the leaves of the tea bush, has been extensively investigated for its antitumor effects. In this review, we summarize the previous literature to elucidate the roles of EGCG in the chemoprophylaxis and therapy of HCC. Accumulating evidence has confirmed EGCG prevents and inhibits the hepatic tumorigenesis and progression through multiple biological mechanisms, mainly involving hepatitis virus infection, oxidative stress, proliferation, invasion, migration, angiogenesis, apoptosis, autophagy, and tumor metabolism. Furthermore, EGCG enhances the efficacy and sensitivity of chemotherapy, radiotherapy, and targeted therapy in HCC. In conclusion, preclinical studies have confirmed the potential of EGCG for chemoprevention and therapy of HCC under multifarious experimental models and conditions. Nevertheless, there is an urgent need to explore the safety and efficacy of EGCG in the clinical practice of HCC.